International Portfolio of Real Estate Investment and Hedging: A Revisit - Addae-Dapaah, Kwame; Sugumaran, Mathan (Archives of Business Research, 2017)
We use office data from ten cities in the Asia-Pacific region from 4Q2001 to 2Q2012 to propose a forward-looking investment appraisal framework to compare the effectiveness of two currency risk hedging strategies for a portfolio of real estate investments in ten cities of seven Asia-Pacific countries. This is aimed at determining the optimal choice among “unhedged”, “artificially” hedged and “natural” hedged options. Analyses based on NPV, IRR, Sharpe Ratio, Jensen’s alpha and stochastic dominance were done for 3, 5 and 7-year holding periods. All the results show that the “natural” hedge strategy is the optimal choice as it provides superior returns.